(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This action research aims to circumvent the continuously increasing number of senior high school students who are cutting classes. This study was performed to enhance the control and organization by disseminating the timetable cards. Its main purpose is to allot help to the Guidance and Counseling Department to bring efficient control and well-organized treatment to students. Cutting classes has a considerable impact on the students academic status. With the help of this study, these students will not have failing grades. The researchers used a descriptive research design in the form of qualitative research and survey method and interview to gather the data needed. An interview was conducted to gather information from five personnel of the Guidance and Counseling Department, and a survey questionnaire was also administered to 90 Grade 12 Accountancy, Business, and Management students from sections 1–18 by using convenience sampling. Based on the results of the study, the Guidance and Counseling Department addressed the factors causing cutting classes of senior high school students in terms of (1) guiding the students in maintaining good attendance and academic performance and (2) guiding the students in maintaining good behavior. Providing time table card in the ID effectively helped the Guidance and Counseling Department to avoid cutting classes of senior high school students. They used timetable cards, which help check the schedule of the students before they are permitted to enter the school premises to easily track the students wearing/changing improper uniforms to cut classes and effectively control the exit and entrance of the students in the school, and (2) regular attendance check, which became helpful in tracking the record of the student’s subject in committing cutting classes (strand, grade level, and section) and in monitoring the attendance students with the improper uniform. The researchers recommended that students should be responsible, considerate, and obliged to follow their class schedules strictly. Students’ attendance must be strictly checked and monitored by the teachers. The school administrators must do continuous counseling and guidance of the students to help them avoid and stop cutting classes. Parents should help their children by encouraging them to excel in school and guiding them in ways that can affect their behavior inside the institution.